40Ar/39Ar ages and geochemical characterization of Cretaceous bentonites in the Nanushuk, Seabee, Tuluvak, and Schrader Bluff formations, North Slope, Alaska. (January 2016) - Shimer, Grant T.; Benowitz, Jeff A.; Layer, Paul W.; McCarthy, Paul J.; Hanks, Catherine L.; Wartes, Marwan
Abstract: Diagenetically altered volcanic ash deposits (bentonites) found in Cretaceous terrestrial and marine foreland basin sediments have the potential to be used for chronostratigraphy and subsurface correlation across Alaska's North Slope. Detailed age and geochemical studies of these volcanogenic deposits may also shed light on the tectonic evolution of the Arctic. Though these bentonites have been previously studied, there are few published results for regional bentonite ages and geochemistry due to challenges of dating weathered volcanic ash. We analyzed mineral separates from cored bentonites recovered from wells in the National Petroleum Reserve Alaska. The analyses confirm that an intense period of volcanic ash deposition on Alaska's North Slope began by the late Albian and persisted throughout the Cenomanian, an interval of rapid progradation and aggradation in the Colville basin. These results also add to a sparse record of radioisotopic ages from the Nanushuk Formation. A bentonite preserved in delta plain sediments in the upper Nanushuk Formation dates to 102.6 ± 1.5 Ma (late Albian), while a bentonite near the base of the overlying Seabee Formation was deposited at 98.2 ± 0.8 Ma, in the early Cenomanian. The two ages bracket a major flooding surface at the base of the Seabee Formation near Umiat, Alaska, placing it near the Albian-Cenomanian boundary (100.5 Ma). Several hundred feet up-section, the non-marine Tuluvak Formation contains bentonites with 40 Ar/ 39 Ar ages of 96.7 ± 0.7 to 94.2 ± 0.9 Ma (Cenomanian), several million years older than previously published K–Ar ages and biostratigraphic constraints suggest. Major and trace element geochemistry of a sub-sample of six bentonites from petroleum exploration wells at Umiat show a range in composition from andesite to rhyolite, with a continental arc source. The bentonites become more felsic from the late Albian (∼102 Ma) to late Cenomanian (∼94 Ma). A likely source for the bentonites is the Okhotsk-Chukotka Volcanic Belt (OCVB) of eastern Siberia, a continental arc which became active in the Albian and experienced episodes of effusivity throughout the Late Cretaceous. Chronostratigraphically anomalous 40 Ar/ 39 Ar ages coincide with peaks of magmatic activity in the OCVB, suggesting that these anomalously old ages may be due to magmatic contribution of xenocrysts or recycling of detrital minerals from older volcanic events. An alternative explanation for the chronostratigraphically anomalous ages is mixing of bentonites with detrital sediment derived from unroofing and erosion of metamorphic rocks in the Brooks Range, Herald Arch, and Chukotka throughout the mid to Late Cretaceous. Highlights: We report the first publicly available 40 Ar/ 39 Ar age for a volcanogenic deposit in the Cretaceous Nanushuk Formation. Volcanic ash preservation in the Colville foreland basin began as early as the Albian and continued throughout the Late Cretaceous. Anomalous 40 Ar/ 39 Ar ages suggest contribution of xenocrysts or contamination with detrital micas from igneous or metamorphic sources.